Economic Issues in the Use of Office Spirometry for Lung Health Assessment. Issue 6 (3rd September 2003) - Krahn, Murray; Chapman, Kenneth R
Abstract : The National Lung Health Education Program (United States) has recently recommended using office spirometry to screen for subclinical lung disease in adult smokers. No published studies evaluate the economic consequences of this recommendation. This review article outlines the issues that must be considered when evaluating the costs and health benefits of office spirometry. Much of the available data on the effectiveness of screening is from studies that included smoking cessation interventions, making it difficult to determine the effects of screening alone. The sensitivity and specificity of screening spirometry are not known, but may not be important in the economic model, because even false positive test results are beneficial if they lead to smoking cessation. Costs to be considered include those of spirometry itself, of implementing and maintaining screening and smoking cessation programs, and of their consequences, ie, reduced morbidity (lower short term health care costs) and mortality (perhaps higher long term health care costs). Despite these unique challenges, data are available to perform economic analyses regarding screening spirometry. Such analyses should play a role in future clinical policy making. Even modest quit rates attributable to screening spirometry may result in highly favourable cost effectiveness ratios.